The Aftermath of the 2008 Global Financial Crisis in the Eastern Caribbean : The Impact on the St Lucia Labor Market - Gimenez, Lea; St. Catherine, Edwin; Karver, Jonathan; Odawara, Rei (World Bank Group, Washington, DC, 2015)
This brief expands the scarce literature on the impact of the global financial crisis on labor market outcomes and welfare in the Organization of Eastern Caribbean States (OECS). The brief focuses on the economy of St. Lucia, one of the OECS member states. The statistical information assembled here should help decision makers and the public in the OECS to develop policy options that can sustain job creation and thereby enhance public welfare. It also can help gauge the effectiveness of policies over time. The evidence presented in this brief shows how the recent financial crisis had significant and long-lasting negative impacts on the welfare of St. Lucians. The government of St. Lucia attempted to use fiscal policy to boost growth and enhance labor market opportunities in the island. Still, unemployed and underemployed St. Lucians together accounted for over 40 percent of the working-age employable population. They suffered a significant decline in welfare in the aftermath of the crisis. They lost not only their income but also the collateral benefits that are often associated with being fully employed in good quality jobs in the “formal” sector of the economy.